D2+ molecular complex in ring-like nanostructures: hydrostatic pressure and electro-magnetic field effects (2014)
ABSTRACT: In this work we investigate the energy states in a D+2 complex formed by the coupling of a conduction band electron and two donor centers in a quantum ring with rectangular cross-section. The in uences of externally applied probes like electric and magnetic elds and hydrostatic pressure together with the change in the relative position between the two Coulombic centers are particularly studied, highlighting the important contribution of the repulsive inter-center interaction. The destruction of the Aharonov Bohm oscillations of the ground state associated with the localization of the electron states in the system is discussed.